Responsibility of Schools in Dispensing Equal Justice: A Singapore Case Study - NATHAN, Rathna (Institutional Knowledge at Singapore Management University, 2011)
The gap between the needs of indigents and the state subsidised legal services or pro bono legal services exist in all societies. Traditionally, the state and the legal fraternity have assumed responsibility to bridge this gap. Law schools have traditionally and culturally confined themselves to the academic instruction of the law. This paper considers whether law schools have an equal responsibility to plug this gap. Four main issues are considered. First, law schools have a professional responsibility to instill legal professionalism in law students, which includes educating students in a pro bono culture. Second, these responsibilities can be effectively discharged by engaging faculty and students in pro bono programs/clinics which have the effect of sensitising law students to social justice issues, advocate legal professionalism and demonstrate professional and community relevance in education. Third, these responsibilities should not merely be justified on the basis of pedagogical relevance and value. Legal curriculum should be improved upon to advance professional responsibilities and a pro bono culture. Fourth, it is important to sustain the pro bono commitment nurtured in law schools. To this end, it is proposed that the Singapore Legal Profession Act, 2009, Cap. 161, § 71, The Legal Profession (Professional Conduct) Rules, (2010) and the Legal Professional Conduct Rules (LPCR) be amended to reflect the professional responsibilities of a lawyer and to encourage dedication of certain number of pro bono hours per annum.